Peran Bahasa dalam Pembentukan Karakter Siswa di Sekolah Dasar SDN 2 Berangah Kabupaten Lombok Tengah Nusa Tenggara Barat - Rayyan Indrawan (Journal of Language Studies, 2025)
Language plays a fundamental role in shaping students' character, particularly at the primary education level where moral and social values begin to form. This study explores how language is used as a medium for character education at SDN 2 Berangah, focusing on everyday interactions between teachers and students, classroom discourse, and school programs that integrate character-building values. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that language is not only a tool for communication but also a key instrument in instilling values such as honesty, respect, responsibility, and cooperation. Teachers consciously use positive and directive language to model good behavior and reinforce desirable attitudes. Additionally, structured language-based activities such as storytelling, reflective dialogue, and moral-themed discussions are found to significantly contribute to students’ moral development. The study concludes that a strategic and consistent use of language within the school environment plays a critical role in developing the students’ character, and suggests that language-focused character education should be strengthened across all subjects and learning contexts.